An electrically switchable visible to infra-red dual frequency cholesteric liquid crystal light shutter. Issue 15 (3rd April 2018) - Lee, Chang Suk; Kumar, Tatipamula Arun; Kim, Jin Ho; Lee, Joong Hee; Gwag, Jin Seog; Lee, Gi-Dong; Lee, Seung Hee
Abstract : Herein, an electrically switchable cholesteric liquid crystal (LC) shutter from visible to infrared light was prepared using a dual frequency LC (DFLC). Abstract : Herein, an electrically switchable cholesteric liquid crystal (LC) shutter from visible to infrared light was prepared using a dual frequency LC (DFLC). The fabricated device is semitransparent to visible and IR light in the planar state and opaque in the focal conic state. Both visible and IR lights are transmitted in the homeotropic state. Interestingly, switching among these states is possible by just varying the voltage and frequency. In addition, it is possible to switch between the planar (homeotropic) and homeotropic (planar) states without going to the focal conic state. The proposed device can even regulate the ambient temperature by controlling the sunlight without losing transparency. Thus, the device is expected to have potential applications as smart windows of automobiles and buildings to control the interior temperature and save energy.